Formation of eutectic and hydrogen absorption/ desorption behavior of heat-treated Ti19Hf4V40Mn35Cr2 alloys. (January 2023) - Liu, Bin; Chen, Xiaoyu; Zhang, Shengbin; Ding, Xin; Chen, Ruirun
Abstract: The effect of high-temperature heat treatment (1673 K, 1min/5min/30min, water quenching) on the microstructure and hydriding/dehydriding properties of Ti19 Hf4 V40 Mn35 Cr2 alloys was studied. Both the proportion and lattice contraction of BCC phases increased after heat treatment. The eutectic (BCC phase + C14 Laves phase) structure was formed under different heat treatment conditions. Ti19 Hf4 V40 Mn35 Cr2 treated at 293 K for 1 min had the highest hydrogen storage capacity (2.23 wt%) and the fastest absorption rate. This was because of the easy and fast diffusion of H atoms. The dehydriding enthalpy ( ΔH ) of the as-cast alloys was 41.70 kJ/mol H2, which was higher than 33.62 kJ/mol H2 of heat-treated alloys. The reason was the decrease in hydride stability. Highlights: The eutectic (BCC phase + C14 Laves phase) structure was found after heat treatment. The effective hydrogen storage capacity reaches 2.23 wt%. Heat treatment improves the maximum hydrogen storage capacity of Ti19 Hf4 V40 Mn35 Cr2 . Heat treatment decreases thermal stability of the hydride.